Assessing quality and productivity of Journal Publications using bibliometric approach: A platform towards world class education - Taib, Che Azlan; Mohammed, Ahmed Hani (School of Technology Management and Logistics (STML), 2019)
Quality and productivity have become increasingly pertinent in the wake of rapid changes that are happening in the marketplace (Nik Mustapha, 1995). Nowadays, these two are still widely accepted as key competitive enablers for organizations in both public and private sectors including the Higher Education Institutions (HEIs). HEIs bear a profound moral responsibility to increase the awareness, knowledge, skills and values needed to create a just and sustainable future (Libunao and Peter, 2013). These institutions are mandated to develop intellectual and conceptual frameworks to achieve these goals. Previous studies, seminars and relevant research has also highlighted the importance of understanding quality and productivity of publications in HEIs. Not withstanding, quality is an elusive concept. In most dictionaries, quality have been defined as a high degree of goodness, a distinguishing characteristic or attribute, a high degree of a high standard of excellence, a high social status, an authorized level of superiority, a regularized, accepted, predetermined and correct level of competence and performance. According to Foster and Ganguly (2013), quality is related with productivity, profitability and sustainability. Summer (2010) in his book wrote that Deming define quality as ‘non-faulty system’, to Juran quality is a concept that needs to be found in all aspects of business and Crosby defined quality as conformance to requirements. In practical wise, some definitions listed by Goetsch and Davis (2014) are (i) quality as performance to the standard expected by the customer, (ii) meeting the customer’s needs the first time and every time, and (iii) doing the right thing right the first time, and always striving for improvement, and always satisfying the customer. Thus, quality can be difficult to comprehend. If we ask 10 people, we may end up with ten different definitions. In Malaysia, quality has been a theme adapted in general by educational providers (Sohail, Rajadurai and Rahman, 2003). In higher educations, quality is the matter about teaching and research (Green, 1994).